2011
DOI: 10.12681/mms.56
|View full text |Cite
|
Sign up to set email alerts
|

Length-Length and Length-Weight Relationships in Nephrops norvegicus from the Aegean Sea (Linnaeus, 1758)

Abstract: The objective of this study was to determine the length-length, length-width and length-weight relationships in Nephrops norvegicus as a basis for conversions. A total of 659 specimens were collected with trawl gears from the commercial trawler Hapulo lu between the 17th and 21st August 2008 in international waters of the middle Aegean Sea. Morphometric equations for the conversions of length and weight were constructed for females, males, and combined sexes. Females were generally smaller than males, and size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These researchers claimed that the size-weight relationships differed significantly as functions of the life habits of the species. The most frequently used dimensions for crustaceans include carapace length, width, body length, body width, and wet weight (AYDIN & AYDIN, 2011). It can be convenient to be able to calculate a particular length measurement when only one of the other length measurements is known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These researchers claimed that the size-weight relationships differed significantly as functions of the life habits of the species. The most frequently used dimensions for crustaceans include carapace length, width, body length, body width, and wet weight (AYDIN & AYDIN, 2011). It can be convenient to be able to calculate a particular length measurement when only one of the other length measurements is known.…”
Section: Discussionmentioning
confidence: 99%
“…It can be convenient to be able to calculate a particular length measurement when only one of the other length measurements is known. The length-weight regression may be used to estimate lengths from weights and vice-versa (ATAR & SECER, 2003;AYDIN & AYDIN, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power equation was applied to analyze the lengthweight relationship (Le Cren 1951;Froese 2006;Graham et al 2009;Jawahir et al 2017), while the linear equation was used to analyze the length-length/width relationship (Chiu and Morton 2001;Aydin and Aydin 2011;Amaral et al 2014;Ming et al 2016). For achieving a better fit of the regression model, an outlier will be removed from the data set (Manimannan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its importance and high economic value as a commercial species in the Atlantic and North Sea [2,3,9], Nephrops has been the subject of several biological and fishery studies , leading to the collection of long time series data for that region. In regard to the Mediterranean Sea, most of the studies have focused on the Western region and the Adriatic sea [7,8,13,15,[30][31][32][33][34][35][36][37][38], with the majority of them within the framework of the EU research project "MEDITS" [39], contrary to even fewer studies in the Eastern Mediterranean and the Aegean Sea [40][41][42][43][44]. The aim of the present study was to fill that knowledge gap in the Eastern Mediterranean, since no such studies were found for the region.…”
Section: Introductionmentioning
confidence: 94%